ASSESSMENT OF NUTRITIONAL STATUS OF PRIMARY SCHOOLS PUPILS IN MOSUL CITY - Bayda A. Yahya (Mesopotamia Journal of Agriculture)
For a period of nine months (October 2003-June 2004), 927 pupils of primary schools, (males and females) in Mosul City were assessed for their nutritional status using nutritional methods and measurements including nutritional history, physical examination (standard chart of weight and height, body mass index) in addition to laboratory estimation of hemoglobin level in blood due to malnutrition. The study aimed at identifying nutritional problems and deficiencies in which nutritional intervention is essential for recovery. The study showed that 58% of primary school pupils were in normal state of nutrition, the remaining 41.7% complaining from malnutrition, 33% of them have mild degree, 1.2% with moderate malnutrition, while over weight diagnosed in 7.5% of student. There were no significant difference between pupils from different socioeconomic levels regarding malnutrition, while over weight showed a high percentage among moderate level group. Related factors to pupils nutritional health diagnosed by this study as: improper nutritional school programs, unhealthy dietary habits among pupils, deficit nutritional educational programs. It has been found that 66% of mild malnourished pupils complaining of anemia. The study suggest a more frequent nutritional surveys at different community's levels, with improvement of nutritional educational programs that emphasize school family participation.